Answer:-3/2
Step-by-step explanation:
-2 2/6+5/6
-7/3 + 5/6
(2x-7+1x5) ➗ 6
(-14+5) ➗ 6
-9 ➗ 6
-9/6=-3/2
Step-by-step explanation:
step by step by solutions are given
check it
hope you like the answer
X=4. Hope this is the one you wanted me to answer.
Answer:
12x + 2
Step-by-step explanation:
Let the number be represented by x.
Then five times the number = 5*x
Seven times the number = 7*x
Sum of 5 times the number minus -2 =
= ![\[5x +2\]](https://tex.z-dn.net/?f=%5C%5B5x%20%2B2%5C%5D)
Adding seven times the number to this expression yields, ![\[5x+2+7x\]](https://tex.z-dn.net/?f=%5C%5B5x%2B2%2B7x%5C%5D)
![\[= (5+7)x+2\]](https://tex.z-dn.net/?f=%5C%5B%3D%20%285%2B7%29x%2B2%5C%5D)
![\[= 12x+2\]](https://tex.z-dn.net/?f=%5C%5B%3D%2012x%2B2%5C%5D)
So the simplified expression corresponds to 12x + 2.
Answer:
4
Step-by-step explanation:
the side Q-R corresponds to K-L
just as O-P corresponds to K-J
K-J= 36
O-P=6
36/6=6
so 24/6=4